Phase transition and tolerance factor relationship of lead-free (Bi0.5K0.5)TiO3-Bi(Mg0.5Ti0.5)O3 piezoelectric ceramics - Jaita P. (2017)
© 2016 Elsevier Ltd and Techna Group S.r.l. A relation between phase transition region and the tolerance factor (t) in BKT-BMgT ceramics was established according to the reported literature for various BKT-based ceramics. In order to confirm the prediction, lead-free piezoelectric ceramics based on (1−x)(Bi 0.5 K 0.50 )TiO 3 -xBi(Mg 0.50 Ti 0.50 )O 3 or (1−x)BKT-xBMgT (x=0.0–0.2) were synthesized by a solid-state reaction method. The compositional dependence of the crystal structure, electrical properties and strain behavior of all ceramics was examined. The crystal structure analysis indicated that the phase transition region was located over the compositional region 0.05 < x < 0.10 (t∼1.0170–1.0130), over which the crystal structure was seen to change from a tetragonal to a pseudo-cubic phase. The tolerance factor of these compositions were closely matched to expected values for the phase transition region in BKT-based ceramics (t∼1.0123–1.0192), as reported in the literatures. The ceramics in these transition region (0.05 < x < 0.10) showed a noticeable enhancement in dielectric constant (ε r =1150–1510, T m =323–347°C), ferroelectric properties (P r =9.7–11.7 μC/cm 2 ) and piezoelectric properties (d 33 =205–225 pC/N) properties, as compared to pure BKT ceramic. Furthermore, the BKT-0.10BMgT sample displayed a high S max =0.22% and d * 33 =314 pm/V which was ∼20–30% higher than that of unmodified-BKT ceramic. The obtained results suggested that a study of the tolerance factor may be employed in a search for the phase transition region with excellent piezoelectric properties in various ceramic systems.